Ethnomedical uses, chemical constituents, and evidence-based pharmacological properties of Chenopodium ambrosioides L.: extensive overview - Kasali, Félicien M.; Tusiimire, Jonans; Kadima, Justin N.; Agaba, Amon G. (Future Journal of Pharmaceutical Sciences, 2021)
The Chenopodium genus is a plant family widely spread worldwide that includes various plant species reputed to possess several medicinal virtues in folk medicines. Chenopodium ambrosioides L. is among the most used plants in traditional medicines worldwide. This review aimed to highlight ethnomedicinal uses, phytochemical status, and pharmacological properties of C. ambrosioides L. Main body of the abstract: The analysis of relevant data highlights various ethnomedicinal uses against human and veterinary diseases in forty countries. Most indications consisted of gastrointestinal tract dysfunctioning troubles and worms parasitemia. Around 330 chemical compounds have been identified in different plant parts, especially in its essential oil fractions (59.84%). However, only a few compounds—mainly monoterpenes and glycosides—have been isolated and characterized. Experimental pharmacological studies validated a large scale of significant health benefits. It appeared that many monoterpenes are antioxidant, insecticidal, trypanocidal, analgesic, antifungal, antiinflammatory, anti-arthritic, acaricidal, amoebicidal, anthelmintic, anticancer, antibacterial, antidiabetic, antidiarrheal, antifertility, antifungal, anti-leishmanial, antimalarial, antipyretic, antisickling, antischistosomal, antiulcer, anxiolytic, immunomodulatory, molluscicidal, and vasorelaxant agents. Short conclusion: Thus, the Chenopodium ambrosioides species necessitates further chemical studies to isolate and new bioactive secondary metabolites and pharmacological investigations to precise the mechanisms of action before clinical trials.
Keywords: Chenopodium ambrosioides; Bioactive compound; Therapeutic indications; Pharmacological bioactivity